2018
DOI: 10.1371/journal.pone.0193948
|View full text |Cite
|
Sign up to set email alerts
|

Rapid activity-dependent modulation of the intrinsic excitability through up-regulation of KCNQ/Kv7 channel function in neonatal spinal motoneurons

Abstract: Activity-dependent changes in the properties of the motor system underlie the necessary adjustments in its responsiveness on the basis of the environmental and developmental demands of the organism. Although plastic changes in the properties of the spinal cord have historically been neglected because of the archaic belief that the spinal cord is constituted by a hardwired network that simply relays information to muscles, plenty of evidence has been accumulated showing that synapses impinging on spinal motoneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
(87 reference statements)
1
18
0
Order By: Relevance
“…The observed changes could also arise from alterations in motoneuron passive membrane properties, such as input resistance; however, these values were not modified by any type of polarization during any of the analysed recording periods. Another possibility is that alterations may occur in the activity levels of several types of ion channels that are responsible for the initiation of ionic currents, such as the M‐current or the Ih current, which might modify the motoneuron f‐I relationship and firing properties (Biel, Wahl‐Schott, Michalakis, & Zong, ; Lombardo, Sun, & Harrington, ) or the channels responsible for the activation of potassium conductance or the inactivation of sodium conductance (Catterall, ). However, in our previous paper (Bączyk et al, ) we showed that DC applications do not change the sag ratio between the peak and plateau R IN values of motoneurons subjected to polarization, indicating unaltered Ih current levels.…”
Section: Discussionmentioning
confidence: 99%
“…The observed changes could also arise from alterations in motoneuron passive membrane properties, such as input resistance; however, these values were not modified by any type of polarization during any of the analysed recording periods. Another possibility is that alterations may occur in the activity levels of several types of ion channels that are responsible for the initiation of ionic currents, such as the M‐current or the Ih current, which might modify the motoneuron f‐I relationship and firing properties (Biel, Wahl‐Schott, Michalakis, & Zong, ; Lombardo, Sun, & Harrington, ) or the channels responsible for the activation of potassium conductance or the inactivation of sodium conductance (Catterall, ). However, in our previous paper (Bączyk et al, ) we showed that DC applications do not change the sag ratio between the peak and plateau R IN values of motoneurons subjected to polarization, indicating unaltered Ih current levels.…”
Section: Discussionmentioning
confidence: 99%
“… 1 5 It is known that KCNQ channels have potential therapeutic value by targeting their activity. 6 , 7 The differentially expressed KCNQ subunits have a direct role in regulating excitability of the neurons that they are distributed. 2 It has been anticipated that by targeting KCNQ channels for development of new drugs on neuronal excitability will be a breakthrough on improving neuronal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the timescale over which the threshold slides to prevent unbounded synaptic growth needs to be much faster than experimentally found [90]. Our proposed Hevent amplitude adaptation operates on the fast timescale of several spontaneous events found experimentally [26,62,50]. Hence, together with the better topography and the resulting event sparsification as a function of developmental stage that the Hebbian rule with adaptive H-events generates, we propose it as the more likely plasticity mechanism to refine receptive fields in the developing visual cortex.…”
Section: Discussionmentioning
confidence: 64%
“…Our adaptation mechanism is consistent with fast intrinsic plasticity operating on the timescale of several spontaneous events supported by many experimental studies. For instance, intrinsic excitability of spine motoneurons is depressed after brief but sustained changes in spinal cord network activity in neonatal mice [50]. Similarly, hippocampal pyramidal neurons also exhibit a rapid reduction of intrinsic excitability in response to sustained depolarizations lasting up to several minutes [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation